Спектральні властивості вібраційного сигналу деталі з тріщиною - Мацько, І.Й.; Кравець, І.Б.; Яворський, І.М. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
Changes of the spectral characteristics of vibration signals from thin cracked blade with crack grows is analyzed in this article. The formulae for cross spectral densities estimates of signal’s stationary components are derived.